2016
DOI: 10.3389/fmicb.2016.00569
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Manuka Honey: No Longer So Alternative

Abstract: Medicinal honey research is undergoing a substantial renaissance. From a folklore remedy largely dismissed by mainstream medicine as “alternative”, we now see increased interest by scientists, clinical practitioners and the general public in the therapeutic uses of honey. There are a number of drivers of this interest: first, the rise in antibiotic resistance by many bacterial pathogens has prompted interest in developing and using novel antibacterials; second, an increasing number of reliable studies and case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
161
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(164 citation statements)
references
References 82 publications
(64 reference statements)
3
161
0
Order By: Relevance
“…A growing body of scientific research, especially on the manuka honey, has recently revealed many molecular mechanisms that may rationalize well known medicinal properties of honey (Carter et al, 2016), and may contribute to expand preventive and even therapeutic uses. Our findings encourage further studies on the Sicilian black honeybee honey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of scientific research, especially on the manuka honey, has recently revealed many molecular mechanisms that may rationalize well known medicinal properties of honey (Carter et al, 2016), and may contribute to expand preventive and even therapeutic uses. Our findings encourage further studies on the Sicilian black honeybee honey.…”
Section: Resultsmentioning
confidence: 99%
“…This study extends knowledge on functional properties of honeys produced by the Sicilian black honeybee assessing their antiradical and antioxidant capacity in several both chemical and biological in vitro models. Thirty samples of monofloral honeys from thirteen botanical species and two honeydew honeys were assayed in comparison with the manuka honey from New Zealand, known as innovative and with specific biomedical properties all over the world (Molan, 1999; Stephens et al, 2010; Carter et al, 2016). With respect to manuka honey, honeys by black honeybee possess remarkable reducing power and antioxidant potential against radicals relevant in dietary foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Lfcin has also been shown to upregulate host defense via the induction of reactive oxygen species that stimulate the fungicidal activities of polymorphonuclear leukocytes (Kullberg et al, 1999). This ability to mount a combined assault on microbial pathogens is a common feature of natural host-derived products, most likely resulting from evolutionary pressures to maintain efficacy and prevent pathogens from developing resistance (Xu et al, 2009; Carter et al, 2016). …”
Section: Structure and Antifungal Activity Of Lactoferricin—the Majormentioning
confidence: 99%
“…Manuka honey (MH) from New Zealand derived from the Leptospermum scoparium tree (Family: Myrtaceae) has been extensively studied for antibacterial and antioxidant activity, as well as for wound healing mechanisms due to a large quantity of physicochemical properties and attractive therapeutic molecules [8,23,24,25,26]. MH contains numerous phenolic compounds, including flavonoids (pinobanksin, pinocembrin, chrysin, luteolin, quercetin, 8-methoxykaempferol, isorhamnetin, kaempferol and galangin) [27], phenolic acids (phenylacetic acid, phenyllacticacid, 4-hydroxybenzoic acid, kojic acid, 2-methoxybenzoic acid, syringic acid, and 4-methoxyphenyllactic acid) and other compounds (methylsyringate, leptosin, glyoxal, 3-deoxyglucosulose and methylglyoxal) [8].…”
Section: Introductionmentioning
confidence: 99%